"It's Just for Us!" Perceived Benefits of Participation in a Group Intervention for Siblings of Children With Cancer. (15th May 2018) - Barrera, Maru; Neville, Alexandra; Purdon, Laura; Hancock, Kelly
Abstract: Objective: This qualitative substudy aimed to investigate the outcomes of sibling group interventions from the perspective of siblings of children with cancer and their caregivers. Method: Siblings were randomized to receive the Siblings Coping Together intervention (SibCT) or attention control (CG). In all, 30 participants, 18 siblings (average age = 11.89 years, 9 CG and 9 SibCT) and 12 caregivers (4 CG and 8 SibCT), were interviewed following group participation. SibCT consists of eight 2-hr manualized sessions delivered weekly; in each session, it combines arts and crafts and cognitive–behavioral strategies structured around a specific theme (family or school). The CG is structured only around arts and crafts. Interviews were analyzed using content analysis. Results: Themes common to both groups included the following: having a group just for siblings, improving family relationships, and feeling reassured of parental role. Themes unique to the SibCT group included the following: learning program targets, increasing self-confidence, feeling less different, and connecting caregivers and siblings through homework. Themes unique to the control group included the following: being a good helper and being in the hospital for positive reasons. Conclusion: This study uncovered additional intervention effects not captured in quantitative measures. Whereas benefits were noted in both groups and speak to the importance of support for siblings in general, positive personal and relational changes unique to siblings in the SibCT group and their caregivers support the importance of specific interventions focused on problem-solving siblings' issues.